2015
DOI: 10.1002/2014rs005592
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cross‐polarization isolation on polarimetric target decomposition and target detection

Abstract: Cross-polarization isolation is one of the key engineering parameters for a polarimetric radar system. Previous studies focused more on the calibration of cross-talk contamination. This paper presents a numerical evaluation of the requirement for cross-polarization isolation from the data users' perspective, i.e., the quantitative impact of polarization cross talk on polarimetric target decomposition and the associated applications such as classification and detection. Sensitivity analyses of several commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
3
11
0
Order By: Relevance
“…The crosstalk error increases the magnitude of the cross-pol images relatively, and the target will be more likely to display volume scattering properties. Most PolSAR applications require that the crosstalk should be less than −32 dB [ 18 ]. Meanwhile, for geophysical parameter inversion research and multitemporal studies over large areas, a higher accuracy is needed, and the crosstalk should be less than −35 dB [ 19 , 20 , 21 ].…”
Section: Polarimetric Error Analysis For the Gf-3 Satellitementioning
confidence: 99%
“…The crosstalk error increases the magnitude of the cross-pol images relatively, and the target will be more likely to display volume scattering properties. Most PolSAR applications require that the crosstalk should be less than −32 dB [ 18 ]. Meanwhile, for geophysical parameter inversion research and multitemporal studies over large areas, a higher accuracy is needed, and the crosstalk should be less than −35 dB [ 19 , 20 , 21 ].…”
Section: Polarimetric Error Analysis For the Gf-3 Satellitementioning
confidence: 99%
“…When light interacts with targets, the polarization of the incident light may undergo a modification, carrying structural information of the targets. Therefore, it is important to characterize the process of the reflective polarization for exploring the polarization distributions and revealing the features of the surface, which can be used in polarization remote sensing [ 9 , 10 ], target detection and recognition [ 11 , 12 , 13 , 14 ], especially in the hidden-target identification. When the sample is not an ideal smooth surface, the reflected light will have different propagating directions, namely scattering.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to evaluating the impact of various distortions on polarimetric parameters from the perspective of applications, there are some studies in the literature [15][16][17] that have focused on the field of terrain surface classification; Wang Y defined the maximum normalized error (MNE) as a generic metric to bridge the system polarization distortion and the polarimetric measurement quality [15]. Guo S [16] then used the MNE to assess the influence of polarization distortion on H/α decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the MNE cannot be directly used in the field of GSR. Another method [17] evaluates the impact of crosstalk contamination by the first-order derivatives of two Cameron parameters of terrain surface classification and man-made target detection. The study suggested that a crosstalk level of −25 dB would be acceptable for these chosen applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation